Verejná správa v slovenskej republike – aktuálne problémy - Neubauerová, Erika; Dubrovina, Nadiya (Univerzita Pardubice, 2010)
The paper deals with structure of public administration in Slovakia and its three parts: government, self-government and public corporations. On the basis of current problems (the impact of the global economic crisis, development of world economy, decentralization process in public administration, elections…) it points to the necessity of changes in public policy.
Keywords: public administration; government; self-government units; public corporations; competence